An assessment into women political participation in Malaysian democratic governance - Okpe, Victor Vincent; Muhammad Fuad Othman; Nazariah Osman (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study assessed the state of women political participation in Malaysian democratic governance. Using descriptive qualitative method, secondary resources like academic books and journal articles, as well as liberal democratic theory as a parameter for analysis to create linkages for sound conclusion, several results emerged. Emerged results disclosed that Malaysian women from the 1957 independence, enjoy their right to vote and contest during elections. Article 8(2) also guaranteed gender equality and avoidance of discrimination or marginalization of citizens including women in their pursuit of political life. Results also showed upward movement or increase in the number of Malaysian women who occupy prominent political offices like the Deputy Prime Minister, Parliamentarians, Members of the Cabinet, Anti-corruption Head, Ministers and Deputy Ministers after the 2018 general elections. Notwithstanding the above upward movement in representation, result also showed that Malaysian women still face a lot of challenges in pursuing their political interest. These challenges as disclosed include male dominance emanating from cultural and religious beliefs, lack of family and spouse supports, poor financial support, absence of political training and marginalization from political parties. The negative indices work against women and must be addressed. They are against the ethics of the liberal democratic theory. To address them, the political leaders must adhere to the constitution and the Beijing Conference 30% advocacy to give Malaysian women their rightful place in politics. The study would benefit the political leaders, women, and researchers. There is the need to also study women political representation in other countries of Asia.